The Contribution of Parents Attention to Student Achievement Motivation - Nofrizal Nofrizal; Herman Nirwana; Alizamar Alizamar (Journal of Educational and Learning Studies, 2020)
The low student achievement motivation is something that must be considered. Parents attention became one of the factors that can influence student achievement motivation. The purpose of this study to describe the contribution of parent attention to student’s achievement motivation in SMK Muhammadiyah 1 Padang. This research uses regression analysis. In the research took the sample of 233 students by using purposive sampling technique. It was used instrument "Wira Solina Parents Attention Scale" with reliability value is 0.888, and "Achievement Motivation Scale" with reliability value is 0.885. The results of research showed that: (1) Parents attention (Mother) in the high category; (2) Parents attention (Father) in the medium category; (3) student achievement motivation in the medium category; (4) the contribution of parents attention (mother) to the achievement motivation is 14.4%; (5) the contribution of the parents attention (father) to the achievement motivation is 12.9%; and (6) the contribution of parents attention (Mother and Father) to the achievement motivation are 15.6%. The results of research showed that parents’ attention (mother and father) need to improved student achievement motivation, so it can be recommended by counselor teacher to give guidance and counseling services in the school and involved their parents to improve student achievement motivation.